The Impact of Financing Quality, Liquidity And Operational Efficiency On BPRS Profitability In NTB - Rio Rio; Muh Jazuli Asyrorroji; Sakinah Mardiyatillah (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2026)
This study examines the challenges faced by Islamic banking in Indonesia, particularly Sharia People's Financing Banks (BPRS), in maintaining profitability amidst rising financing risks and operational cost pressures. The research aims to analyze the impact of Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Expenses to Operating Income Ratio (BOPO) on profitability, measured by Return on Assets (ROA), at three BPRS in West Nusa Tenggara from Q1 2020 to Q3 2025. A panel data regression approach with a Fixed Effect model and bootstrap standard error estimation was employed. The results show that NPF and BOPO have a significant negative effect on ROA, while FDR has an insignificant impact. The study contributes new insights into the relationship between financing quality, operational efficiency, and profitability, offering practical recommendations for risk management and cost efficiency in Islamic microfinance institutions.